Answer: -7 -7
-5 -5
-3 -3
-1 -1
Explanation:
To fill in the table, just substitute x into 2x-3 for each row.
x = -2
So for the first row, 2x - 3 = 2(-2) - 3 = -4 - 3 = -7 so for both columns 2x - 3, and y, fill in -7 for both columns on the row where x = -2
x = -1
So for the second row, 2x - 3 = 2(-1) - 3 = -2 - 3 = -5 so for both columns 2x - 3, and y, fill in -5 for both columns on the row where x = -1
x = 0
So for the third row, 2x - 3 = 2(0) - 3 = 0 - 3 = -3 so for both columns 2x - 3, and y, fill in -3 for both columns on the row where x = 0
x = 1
So for the last row, 2x - 3 = 2(1) - 3 = 2 - 3 = -1 so for both columns 2x - 3, and y, fill in -1 for both columns on the row where x = 1